Altered central and peripheral haemodynamics during rhythmic handgrip exercise in young adults with SARS-CoV-2 - Stute, N. L.; Stickford, A. S. L; Stickford, J. L.; Province, V. M; Augenreich, M. A.; Bunsawat, K.; Alpenglow, J. K.; Wary, D. W.; Ratchford, S. M. (Experimental Physiology, 2022)
The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can have a profound impact on vascular function. While exercise intolerance may accompany a variety of symptoms associated with SARS-CoV-2 infection, the impact of SARS-CoV-2 on exercising blood flow (BF) remains unclear. Central (photoplethysmography) and peripheral (Doppler ultrasound) haemodynamics were determined at rest and during rhythmic handgrip (HG) exercise at 30% and 45% of maximal voluntary contraction (MVC) in young adults with mild symptoms 25 days after testing positive for SARS-CoV-2 (SARS-CoV-2: n = 8M/5F; age: 21 ± 2 years; height: 176 ± 11 cm; mass: 71 ± 11 kg) and were cross-sectionally compared with control subjects (Control: n = 8M/5F; age: 27 ± 6 years; height: 178 ± 8 cm; mass: 80 ± 25 kg). Systolic blood pressure, end systolic arterial pressure and rate pressure product were higher in the SARS-CoV-2 group during exercise at 45% MVC compared with controls. Brachial artery BF was lower in the SARS-CoV-2 group at both 30% MVC (Control: 384.8 ± 93.3 ml min-1; SARS-CoV-2: 307.8 ± 105.0 ml min-1; P = 0.041) and 45% MVC (Control: 507.4 ± 109.9 ml min-1; SARS-CoV-2: 386.3 ± 132.5 ml min-1; P = 0.002). Brachial artery vascular conductance was lower at both 30% MVC (Control: 3.93 ± 1.07 ml min-1 mmHg-1; SARS-CoV-2: 3.11 ± 0.98 ml min-1 mmHg-1; P = 0.022) and 45% MVC (Control: 4.74 ± 1.02 ml min-1 mmHg-1; SARS-CoV-2: 3.46 ± 1.10 ml min-1 mmHg-1; P < 0.001) in the SARS-CoV-2 group compared to control group. The shear-induced dilatation of the brachial artery increased similarly across exercise intensities in the two groups, suggesting the decrease in exercising BF may be due to microvascular impairments. Brachial artery BF is attenuated during HG exercise in young adults recently diagnosed with mild SARS-CoV-2, which may contribute to diminished exercise capacity among those recovering from SARS-CoV-2 like that seen in severe cases.